The importance of medical literature monitoring in pharmacovigilance - achievements and challenges - Stoiljković, Miloš; Pejović, Gordana (Archives of Pharmacy, 2022)
According to the U.S. Food and Drug Administration (FDA), scientific and medical literature is among the four largest sources of adverse drug reactions (ADR) reporting. The aim of this work was to highlight the growing potential of medical literature search in conducting pharmacovigilance (PV) activities, summing up the most common challenges facing pharmaceutical industry in this field. A special emphasis was given to examination of Individual Case Safety Reports (ICSRs) publication frequency in medical literature over the past 15 years in the Republic of Serbia. A comprehensive review of published scientific papers, national and international PV guidance’s, and screening of websites of the relevant Contract Research Organizations experienced in medical literature monitoring for PV purposes has been carried out. Individual cases of ADRs published by Serbian authors in relevant medical journals have been identified by conducting a global Embase search. A significant overall increase in the number of case reports was identified. This showed a positive correlation with the number of ADR reports. Systematic review of medical literature appears to be an important tool especially for signal detection (1). In Serbia, a significant increase of ICSR literature reports has been recorded since 2010, mostly as the result of improvements in applying a good PV practice and the increasing development and availability of modern communication channels and global database use (2). However, adequate selection of local, non-indexed medical literature still appears to be one of the biggest challenges for pharmaceutical industry given the lack of clear regulatory guidance’s.